N-3 Fatty acids affect haemostasis but do not increase the risk of bleeding: clinical observations and mechanistic insights. Issue 9 (14th May 2014) - Wachira, John K.; Larson, Mark K.; Harris, William S.
<x content-type="archive" xml:space="preserve">Abstract</x> n-3 Fatty acids (EPA and DHA, from fish oil) are essential fatty acids that are approved for the treatment of severe hypertriacylglycerolaemia and, in some countries, used for reducing the risk of CVD. Because of their inhibitory effects on platelet function, some practitioners have, perhaps unnecessarily, discontinued their use in patients undergoing invasive procedures or being treated with anti-platelet or anticoagulation drugs. Thus, the aim of the present study was to review the effects of n-3 fatty acids on bleeding complications in a wide variety of clinical settings, and to summarise their biochemical mechanism of action in platelet function and coagulation. We surveyed recent publications that either directly studied the effects of n-3 fatty acids on the risk of bleeding or focused on different end-points and also reported the effects on bleeding. n-3 Fatty acid treatment had no effect on the risk of clinically significant bleeding in either monotherapy or combination therapy settings. Although originally believed to operate primarily via the cyclo-oxygenase system, these fatty acids have been shown to affect multiple signalling pathways and thrombotic processes beyond simply affecting platelet aggregation. The present overview found no support for discontinuing the use of n-3 fatty acid treatment before invasive procedures or when given in combination with other agents that affect bleeding. On the contrary, the use of these fatty acids in several settings improved clinical outcomes.